Engineering a Single-Agent Cytokine/Antibody Fusion That Selectively Expands Regulatory T Cells for Autoimmune Disease Therapy - Spangler, Jamie B; Trotta, Eleonora; Tomala, Jakub; Peck, Ariana; Young, Tracy A; Savvides, Christina S; Silveria, Stephanie; Votavova, Petra; Salafsky, Joshua; Pande, Vijay S; Kovar, Marek; Bluestone, Jeffrey A; et al. (Journal of immunology (Baltimore, Md., 2018)
IL-2 has been used to treat diseases ranging from cancer to autoimmune disorders, but its concurrent immunostimulatory and immunosuppressive effects hinder efficacy. IL-2 orchestrates immune cell function through activation of a high-affinity heterotrimeric receptor (composed of IL-2Rα, IL-2Rβ, and common γ [γc]). IL-2Rα, which is highly expressed on regulatory T (TReg) cells, regulates IL-2 sensitivity. Previous studies have shown that complexation of IL-2 with the JES6-1 Ab preferentially biases cytokine activity toward TReg cells through a unique mechanism whereby IL-2 is exchanged from the Ab to IL-2Rα. However, clinical adoption of a mixed Ab/cytokine complex regimen is limited by stoichiometry and stability concerns. In this study, through structure-guided design, we engineered a single agent fusion of the IL-2 cytokine and JES6-1 Ab that, despite being covalently linked, preserves IL-2 exchange, selectively stimulating TReg expansion and exhibiting superior disease control to the mixed IL-2/JES6-1 complex in a mouse colitis model. These studies provide an engineering blueprint for resolving a major barrier to the implementation of functionally similar IL-2/Ab complexes for treatment of human disease.
Keywords: autoimunitní nemoci; kultivované buňky; Antibodies; Protein Engineering; protilátky; kolitida; proteinové inženýrství; cytokiny; Disease Models, Animal; Receptors, Interleukin-2; regulační T-lymfocyty; Mice; Cell Proliferation; Cytokines; Autoimmune Diseases; T-Lymphocytes, Regulatory; Cells, Cultured; aktivace lymfocytů; modely nemocí na zvířatech; imunoterapie; zvířata; Humans; Lymphocyte Activation; Recombinant Fusion Proteins; rekombinantní fúzní proteiny; myši; Immunotherapy; proliferace buněk; Colitis; receptory interleukinu-2; lidé; Animals